2014
DOI: 10.1016/j.mee.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental verification of heat dissipation mechanisms in an SU-8 electrothermal microgripper

Abstract: NOTICE: this is the author's version of a work that was accepted for publication in Microelectronic Engineering. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Microelectronic Engineering, 124, 25 July 2014, 10.1016/j.mee.2014.06.002. Additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In other work reported previously, we have modelled and experimentally verified the heat loss mechanism in the microgripper [16], performed further heat loss studies in different ambient gases over a range of pressures [17] and demonstrated the use of the microgripper in holding a cell while simultaneously being able to detect and quantify the excretion of potassium ions using an ion specific electrode fabricated as an integral part of the structure [18].…”
Section: Introductionmentioning
confidence: 71%
“…In other work reported previously, we have modelled and experimentally verified the heat loss mechanism in the microgripper [16], performed further heat loss studies in different ambient gases over a range of pressures [17] and demonstrated the use of the microgripper in holding a cell while simultaneously being able to detect and quantify the excretion of potassium ions using an ion specific electrode fabricated as an integral part of the structure [18].…”
Section: Introductionmentioning
confidence: 71%
“…For silicon materials, both the coherence length and wavelength are at the nanoscale, whereas the feature size of the electrothermal microgripper is at the micron scale and larger than the coherence length and wavelength. Therefore, the continuous medium hypothesis is still applicable to heat radiation, as is the classical radiation transport model Stefan-Boltzmann law [ 18 ].…”
Section: Analysis Of the Heat Transfer Mechanism And Modellingmentioning
confidence: 99%
“…In other words, large output forces can be produced by applying relatively low voltages (below 10 V) [13,14]. Electrothermal actuators have been widely deployed for microgripping applications [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%